Alterations in glucocorticoid negative feedback following maternal Pb, prenatal stress and the combination: A potential biological unifying mechanism for their corresponding disease profiles - Rossi-George, A. (2009)
Combined exposures to maternal lead (Pb) and prenatal stress (PS) can act synergistically to enhance behavioral and neurochemical toxicity in offspring. Maternal Pb itself causes permanent dysfunction of the body's major stress system, the hypothalamic pituitary adrenal (HPA) axis. The current study sought to determine the potential involvement of altered negative glucocorticoid feedback as a mechanistic basis of the effects in rats of maternal Pb (0, 50 or 150 ppm in drinking water beginning 2 mo prior to breeding), prenatal stress (PS; restraint on gestational days 16-17) and combined maternal Pb + PS in 8 mo old male and female offspring. Corticosterone changes were measured over 24 h following an i.p. injection stress containing vehicle or 100 or 300 μg/kg (females) or 100 or 150 μg/kg (males) dexamethasone (DEX). Both Pb and PS prolonged the time course of corticosterone reduction following vehicle injection stress. Pb effects were non-monotonic, with a greater impact at 50 vs. 150 ppm, particularly in males, where further enhancement occurred with PS. In accord with these findings, the efficacy of DEX in suppressing corticosterone was reduced by Pb and Pb + PS in both genders, with Pb efficacy enhanced by PS in females, over the first 6 h post-administration. A marked prolongation of DEX effects was found in males. Thus, Pb, PS and Pb + PS, sometimes additively, produced hypercortisolism in both genders, followed by hypocortisolism in males, consistent with HPA axis dysfunction. These findings may provide a plausible unifying biological mechanism for the reported links between Pb exposure and stress-associated diseases and disorders mediated via the HPA axis, including obesity, hypertension, diabetes, anxiety, schizophrenia and depression. They also suggest broadening of Pb screening programs to pregnant women in high stress environments. © 2008 Elsevier Inc. All rights reserved.